Habib Husein Ja'far Al-Hadar's Innovative Da'wah Style Through Social Media - Khafiyah Muslihatun Nisa (Konsultan Jurnal Ilmiah Indonesia, 2024)
Modern rhetoric includes a strong memory, high creative and fantasy power, appropriate expression techniques and the power of proof and correct judgment, so it can be concluded that Rhetoric is a field of science that studies or questions how to speak which has a charming appeal, so that people who listen to it can understand and be moved by their feelings. Almost all preachers use interesting rhetoric so that the preaching is conveyed well. According to Habib Husein Jafar: